Analysis of process of self-driven design activity based on designer's intrinsic motivation: case study of a professional graphic designer. Issue 3 (2nd July 2020) - Takashima, Kentaro; Senoo, Dai
ABSTRACT: Intrinsic motivation is an important factor in design activity as it plays a role in achieving creative design outcomes. Previous studies suggested that designers can spontaneously initiate design activity even without the identification of a customer problem or need. The purpose of this study was to clarify the characteristics of the process underlying self-driven design activity based on the designer's intrinsic motivation. In a case study targeting a professional graphic designer, we compared her process of self-driven design activity with that of customer-driven design activity aimed at solving a given customer problem. We compared both processes from two viewpoints: the sequence of actions and the decision-making strategy. During the design process, data were collected regularly using a question-based method and weekly using a retrospective-report method. The results suggest that the self-driven design activity process is an iteration of information gathering and idea sketching, whereas the customer-driven design activity process is a linear combination of actions. The designer starts information gathering without a clear customer problem and frequently switches among actions even late in the process. The results indicate that managers should support resource collection and allow flexibility of action even late in the process to improve self-driven design activity.